Advantages and Contributions in The Balanced Scorecard Implementation. Intangible Capital - Quesado, Patricia (2018)
Purpose: In this paper we aim to identify and analyse a set of advantages and contributions derived from the Balanced Scorecard (BSC) implementation. Design/methodology: In order to answer the research question, we have carried out a qualitative research based on the exclusively bibliographical review of theoretical / conceptual and empirical works previously done on the subject (systematic review of the literature). Findings: The results allow us to conclude that the BSC is more than a simple performance evaluation system, to become a true strategic management tool able to clarify and translate the mission and organizational strategy, making possible the communication process, the strategic alignment and the organizational learning. Originality/value: The study presents a contribution to the current state of knowledge, since the identification of the advantages and contributions in the BSC introduction and implementation can facilitate its adoption and development in the organizations that intend to implement this tool. In addition, a theoretical basis is provided for subsequent research, evidencing the breadth of research on the topic studied.